THE VOICE OF THE VOICELESS: COUNTERING THE FESTIVAL AND ELEVATING REYOG OBYOKAN AS CULTURAL CAPITAL - Tallapessy, Albert; Setiawan, Ikwan (Paradigma: Jurnal Kajian Budaya, 2024)
This article examines two performance models of Reyog Ponorogo: the festival model and the obyokan model. These two competing models represent differing perspectives on one side, the interests of the artists and the community, and on the other, the interests of the state. By applying cultural studies theories, particularly those of representation and hegemony, this study analyzes data collected through observations of Reyog performances at both festival and obyokan events, as well as interviews with artists and community members. The findings reveal that the obyokan model emphasizes an egalitarian spirit, allowing artists greater aesthetic freedom and providing the community with a sense of belonging in Reyog culture. In contrast, the festival model has historically been associated with the state's efforts to impose order on Reyogartists and choreographies, while simultaneously promoting tourism in Ponorogo.